Chemometrics Application for Grouping and Determinating Volatile Compound which related to Antioxidant Activity of Turmeric Essential Oil (Curcuma longa L) - Rosy Islamadina; Adelin Can; Abdul Rohman (LPPT Universitas Gadjah Mada, 2020)
Turmeric essential oil is known to have antioxidant activity. Various in vitro antioxidant activity assays has been carried out. Related to this research, it tries to examine the antioxidant potential of turmeric essential oil and see the composition that is responsible for antioxidant activity combine with chemometrics. The research method used was a narrative review of 60 articles obtained from several databases. The review conducted on profiling essential oil compounds that identified using GC-MS and evaluation of the antioxidant activity of turmeric essential oil with the most commonly used method including scavenging radical 2,2 diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis (3-ethylbenzothiazoline-6 sulfonic acid (ABTS). Analysis methods used for grouping various multivariate data subjects and determaining the relationship between the variables were Principal Component Analysis (PCA) and Cluster Analysis (CA). According to the review, turmeric essential oils are proven to have potential antioxidant activity and have variations in chemical contents. PCA was success for grouping subjects with various correlated variables, determining variables wich the most influential and correlation between variables. CA method can be used to group samples without requiring mutually correlated variables.